Manajemen Risiko Keamanan Aset Teknologi Informasi di DISKOMINFOSANDITIK Kabupaten Sumedang Menggunakan ISO 31000:2018 - Irma Rahayu; David Setiadi; Dwi Yuniarto (Pusat Riset dan Inovasi Nasional, 2025)
The Sumedang Regency Communication and Informatics, Coding and Statistics Service is a government agency that utilizes information technology to support its operational activities. This research examines how security risks are managed for information technology assets in the Department. The risk management approach used in this research refers to ISO 31000:2018. The main objective of this research is to evaluate the extent to which the implementation of the ISO 31000:2018 standard is effective in protecting IT assets and minimizing risks that could disrupt smooth operations. The methodology used includes identification, analysis, evaluation and risk management. The identification results show that there are 14 potential risks, consisting of 7 low level risks, 3 medium level risks, and 4 high level risks. Risks in the high category require more attention, especially those related to power outages, which are recommended to be overcome by installing an automatic generator.